The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/app9163356
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Micro-Scale Diffusion Combustion: A Brief Review

Abstract: With the increasing global concerns about the impacts of byproducts from the combustion of fossil fuels, researchers have made significant progress in seeking alternative fuels that have cleaner combustion characteristics. Such fuels are most suitable for addressing the increasing demands on combustion-based micro power generation systems due to their prominently higher energy density as compared to other energy resources such as batteries. This cultivates a great opportunity to develop portable power devices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…The design and manufacture of micro burners, which have dimensions at the millimeter or submillimeter level, pose unique challenges when compared to conventional combustors, which make it not trivial to obtain a stable flame, as documented in Hossain and Nakamura [10], Ju and Maruta [1], Nakamura et al [2], Resende et al [11], and Lee et al [12]. These challenges extend to combustion in microscale environments, where the effects of viscosity are amplified in small channels, the physical residence time of mixed gases is shortened, and the ratio of area to volume of the combustion chamber increases sharply [13,14].…”
Section: Challenges Within Microcombustionmentioning
confidence: 99%
“…The design and manufacture of micro burners, which have dimensions at the millimeter or submillimeter level, pose unique challenges when compared to conventional combustors, which make it not trivial to obtain a stable flame, as documented in Hossain and Nakamura [10], Ju and Maruta [1], Nakamura et al [2], Resende et al [11], and Lee et al [12]. These challenges extend to combustion in microscale environments, where the effects of viscosity are amplified in small channels, the physical residence time of mixed gases is shortened, and the ratio of area to volume of the combustion chamber increases sharply [13,14].…”
Section: Challenges Within Microcombustionmentioning
confidence: 99%
“…This type of system needs external power supply and, given the typical battery limitations, efforts have been made to develop alternatives based on microcombustion in order to take advantage of the high-density energy of the hydrocarbon and hydrogen fuels. Nevertheless, early experimental studies involving microcombustion presented some difficulties to obtain a stable flame caused mainly by two phenomena: the low residence time inside of the microcombustor to complete combustion and the higher heat losses from the combustion chamber walls [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study [28], combustion characteristics were analyzed for syngas laminar micro diffusion flames. Resende et al [29] summarized the numerical studies on micro diffusion combustion flame. The review concluded that the numerical simulations are capable of predicting the micro diffusion flame behavior both quantitatively and qualitatively.…”
Section: Introductionmentioning
confidence: 99%